Designing and conducting mixed methods research - Creswell, John W. (Sage, 2011)
This book was exactly what I needed for the methods section in my thesis proposal. I recommend this book to any graduate student needing to know about mixed methods research in depth. It even provides examples on how to write purpose statements depending on which specific mixed methods design type that you use.